Teachers' Personal and Collective Work-Identity Predicts Exhaustion and Work Motivation: Mediating Roles of Psychological Job Demands and Resources - Nordhall, Ola; Knez, Igor; Saboonchi, Fredrik; Willander, Johan (Frontiers in Psychology, 2020)
The aim of this study was to investigate the mediating roles of teachers' psychological job demands and resources regarding personal and collective work-identity, respectively, and exhaustion and self-determined work motivation, respectively. A total of 2,905 members of a Swedish teacher's trade union received an online questionnaire by e-mail; 768 individuals answered the questionnaire and so participated in this study. The data were obtained by self-reported measures (e.g., emotional and cognitive components of work-identity, psychological job demands and resources, exhaustion and work motivation) and analyzed by mediation regression analyses. The results showed that teachers' psychological job demands (prosocial extra-role performance) mediated relationships between cognitive personal work-identity and emotional collective work-identity, respectively, and exhaustion. Teachers' psychological job resources (educational inspiration) mediated relationships between emotional personal work-identity and cognitive collective work-identity, respectively, and self-determined work motivation. Thus, teachers might be disadvantaged by stronger personal work-related thinking and collective work-related feeling when related to exhaustion, to some extent accounted for by psychological job demands, and they might find advantage in stronger personal work-related feeling and collective work-related thinking when related to work motivation, to some extent accounted for by psychological job resources.